PENGEMBANGAN MEDIA BERBASIS GENIALLY PERMAINAN ULAR TANGGA PADA MATERI STANDAR PELAYANAN CUSTOMER SERVICE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI BISNIS RITEL DI SMK ADHIKAWACANA SURABAYA - Irma Tri Mustika; Veni Rafida (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This research was motivated by the low learning outcomes of Grade XI Retail Business students at SMK Adhikawacama Surabaya, where 69% had not achieved the Minimum Mastery Criteria (KKM) on Customer Service Standards material due to lecture-based methotds and non-interactive media. This study aimed to develop a Genially-based snakes and ladders game media, measure its feasibility, and analyze students’learning outcome improvement. The Research and Development (R&D) method with the 4D model was employed, involving 30 students of Grade XI Retail Business 2 as trial subjects. The results showed that the media was feasible with an average expert validation of 80,33%, practical based on student response questionnaires at 81,60% categorized as “Very Positive”, and effective in improving learning outcomes with an average N-Gain Score of 0,379 categorized as “Moderate”.